Expression level of sonic hedgehog correlated with the speed of gastric mucosa regeneration in artificial gastric ulcers. Issue 4 (April 2014) - Tanaka, Takeshi; Arai, Makoto; Minemura, Shoko; Oyamada, Arata; Saito, Keiko; Jiang, Xia; Tsuboi, Masaru; Sazuka, Sayuri; Maruoka, Daisuke; Matsumura, Tomoaki; Nakagawa, Tomoo; Sugaya, Shigeru; et al.
Abstract Background and Aim Gastric ulcer healing is a complex process involving cell proliferation and tissue remodeling. Sonic hedgehog (Shh) activates the Shh signaling pathway, which plays a key role in processes such as tissue repair. Shh and interleukin 1β (IL1β) have been reported to influence the proliferation of gastric mucosa. We evaluated the relationships between the speed of gastric ulcer healing and the levels of expression of Shh and IL1β. Methods The study included 45 patients (mean age 71.9 ± 9.0 years; M/F, 30/15) who underwent endoscopic submucosal dissection (ESD) for gastric cancer, followed by standard dose of oral proton‐pump inhibitor for 4 weeks. Subsequently, the size of ESD‐induced artificial ulcers were measured to determine the speed of gastric ulcer healing, and regenerating mucosa around the ulcers and appropriately matched controls were collected from patients by endoscopic biopsy. Polymerase chain reaction (PCR) array analysis of genes in the Shh signaling pathway was performed, and quantitative reverse transcription (RT)‐PCR was used to measure IL1β mRNA. Results The levels of Shh and IL1β mRNA were 3.0 ± 2.7‐fold and 2.5 ± 2.5‐fold higher, respectively, in regenerating mucosa of artificial ulcers than in appropriately matched controls, with the two being positively correlated (r = 0.9, P < 0.001). Shh (r = 0.8, P < 0.001) and IL1β (r = 0.7, P < 0.005) expression was each positively correlated with the speed of gastric ulcer healing, but multivariate analysis showed that Shh expression was the only significant parameter (P = 0.045). Conclusions Expression of Shh was correlated with the speed of gastric ulcer healing, promoting the regeneration of gastric mucosa.